An Empirical Study Of Application Of Labor Laws In Industrial Undertakings (Journal of Namibian Studies : History Politics Culture, 2023)
This paper investigates the implementation of labor laws in industrial undertakings in Chhattisgarh, using a survey approach with 572 respondents. The research focuses on five factors: wages and remuneration, work conditions, health, safety and welfare, equality of treatment and social security. The study also examines the satisfaction level of workers regarding the application of labor laws in public and private industrial undertakings.